2017
DOI: 10.1002/jctb.5241
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement and optimization of photocatalytic cyanide degradation in aqueous solution using Zn (II) and Fe (III) oxides as nanostructure supported on activated carbon

Abstract: BACKGROUND: Cyanide is a toxic compound used in gold mining, steel, electroplating and chemical industries. In this research, different mole ratios of Fe 3+ /ZnO supported on powder activated carbon (PAC) in the presence of H 2 O 2 under UV irradiation were used to degrade cyanide contamination. The photocatalyst was characterized by XRD, XRF, FESEM, TEM and BET and response surface methodology was applied to assess the individual and interaction effects of several operating factors on cyanide degradation effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Further, modification of AC with other materials especially TiO 2 , ZnO, and Fe 2 O 3 significantly improved the adsorption capacity and the cyanide removal yield. Most of these modified activated carbonbased materials not only can be used as a promising adsorbent but also as a high photoactive catalyst (Eskandari et al 2017(Eskandari et al , 2019. The research findings also verify that an adsorption process benefits from using low cost and ecofriendly bioadsorbents prepared from agricultural waste materials as the studies of (Dwivedi et al 2016;Moussavi and Khosravi 2010) showed cyanide (100 mg/L) removal by using 1.5 g/L of pistachio hull waste as an effective bioadsorbent was obtained 99% after 1 h and cyanide was removed by 87 and 82% using 20 g/L of bioadsorbents of PAS and TGL after 2 h, respectively.…”
Section: Comparison Of Different Methods Of Cyanide Removalmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, modification of AC with other materials especially TiO 2 , ZnO, and Fe 2 O 3 significantly improved the adsorption capacity and the cyanide removal yield. Most of these modified activated carbonbased materials not only can be used as a promising adsorbent but also as a high photoactive catalyst (Eskandari et al 2017(Eskandari et al , 2019. The research findings also verify that an adsorption process benefits from using low cost and ecofriendly bioadsorbents prepared from agricultural waste materials as the studies of (Dwivedi et al 2016;Moussavi and Khosravi 2010) showed cyanide (100 mg/L) removal by using 1.5 g/L of pistachio hull waste as an effective bioadsorbent was obtained 99% after 1 h and cyanide was removed by 87 and 82% using 20 g/L of bioadsorbents of PAS and TGL after 2 h, respectively.…”
Section: Comparison Of Different Methods Of Cyanide Removalmentioning
confidence: 99%
“…The further investigation of the results of Table 6 shows that while some methods of cyanide removal like ozone (O 3 ) injection only degraded cyanide by 30%, the combination of O 3 with activated carbon adsorption technology could substantially enhance the degradation efficiency as cyanide was removed completely in a combined treatment system (Sánchez-Castillo et al 2015). As can be seen in Table 6, the performance of an adsorption process with photolysis (UV) and H 2 O 2 was also compared and the results indicated that using activated carbon or modified activated carbon adsorbents was more beneficial to purify wastewater containing cyanide than using UV, H 2 O 2 or the combination of these two (UV/H 2 O 2 ) that only degraded cyanide by 12, 8 and 33%, respectively (Eskandari et al 2017). The comparison of adsorption process by photocatalysis implies that both remediation technologies have strong potential to remove cyanide effectively.…”
Section: Comparison Of Different Methods Of Cyanide Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…The third strategy consists of coupling two semiconductors. The oxidation of the sacrificial agent or H 2 O and the reduction of hydrogen can be carried out on one of the semiconductors, whereas the other one can contribute to (i) enhancing the separation and transport of the electron–hole pairs, (ii) sensitizing the photocatalyst to visible light or, (iii) acting as co‐catalyst such as CdS/TiO 2 or TiO 2 /PbS . If redox reactions occur one in each semiconductor, the structure is called a Z‐scheme.…”
Section: Influence Of System Units On Photocatalytic Performancementioning
confidence: 99%